Nanomechanical fingerprints of individual blocks of a diblock copolymer chain - Gunari, Nikhil (Langmuir : the ACS journal of surfaces and colloids, 2008)
Atomic force microscopy (AFM)-based single polymer chain pulling experiments have been used to study the structural transitions of individual homopolymer chains in water. Polystyrene (PS) showed a three-regime force-extension profile exhibiting a force plateau reminiscent of a first-order transition, as predicted theoretically, whereas poly(methyl methacrylate) (PMMA) showed a characteristic saw-tooth pattern reminiscent of multidomain disassembly behavior. The two distinct structural transtions provide fingerprints for the individual homopolymers, which can be used to identify individual blocks of symmetric and asymmetric PS- b-PMMA diblock copolymer chains